The case for Trump [compact disc, unabridged] - Hanson, Victor Davis (Hachette Audio, 2019)
Explains how a celebrity businessman with no political or military experience triumphed over sixteen Republican rivals and a well-funded Democrat and argues that Trump's outsider status has made him a successful president.